P227 Timing of acute severe colitis in the course of an inflammatory bowel disease: is it a prognostic factor?. (27th May 2021) - Sahar, N; Dahmani, W; Nour, E; Aya, H; Wafa, B A; Aida, B S; Ahlem, B; Mehdi, K; Hanene, J; Ali, J
Abstract: Background: In this study, we aimed to compare outcomes of patients with a severe acute colitis (SAC) inaugurating their inflammatory bowel disease (IBD) with SAC occurring in those with Known diagnosis of IBD. Methods: We conducted a retrospective chart review of patients who were admitted to our unit for severe acute colitis over 7 years. Demographics, characteristics of the disease, clinical presentation, laboratory, morphologic investigations, treatments and outcomes were reviewed from medical records. Patients were divided in two groups: SAC inaugurating IBD (A) and SAC occurring during the course of Known IBD (B) and compared in terms of clinical presentation, response to medical treatment and colectomy rate. Statistical analysis was performed with SPSS software version 19. Results: A total of 62 patients were colliged (23 males and 39 females). Mean age at the onset of SAC was 36 years (14–78 years). There were 34 patients of group (A) and 28 patients of group (B). Overall, there were 28 patients with Crohn's disease, 31 patients with UC and 3 others with indetermined colitis. There were no differences between both of the groups with regard to sex, age at the onset of SAC, smoking status, family history of IBD, body mass index and laboratory findings including full blood count and C reactive protein. Mean Truelove–Witts score was higher in group A vs group B (4 Vs 3, p<0.0001). Erythrocyte sedimentation rate was slightly higher in group A than group B (68 Vs 53, p=0.07). Overall, endoscopic signs of severity were significantly more common in patients from group A vs group B: deep colonic ulcerations (p=0.05) and diffuse mucosal abrasions (p=0.04). Patients from group B seem to respond better to steroid therapy than patients from group A (68% Vs 58%, p=0.5). There was no difference between both of the groups with regard to use of cyclosporine, colectomy, and recurrence of SAC. Conclusion: Patients with severe acute colitis inaugurating their IBD seemed to have more severe clinical presentation than in those followed for IBD and complicated by SAC. However, response to therapy and need for colectomy are similar in both groups.